2007
DOI: 10.7326/0003-4819-147-1-200707030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcomes in Pregnant Women with Acute Hepatitis E Virus Infection

Abstract: Pregnant women with jaundice and acute viral hepatitis caused by HEV infection had a higher maternal mortality rate and worse obstetric and fetal outcomes than did pregnant women with jaundice and acute viral hepatitis caused by other types of viral hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
339
13
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(385 citation statements)
references
References 18 publications
24
339
13
9
Order By: Relevance
“…Maternal mortality rates of about 25% in association with fulminant hepatic failure have been observed in HEV‐infected pregnant women,18 and the human placenta was also implicated as an extrahepatic replication site of HEV. Notably, vertical transmission has been shown to occur frequently,19 and adverse fetal outcome, especially in the third trimester, include preterm delivery, abortion, stillbirth, and intrauterine fetal and neonatal death 18, 20, 21. However, the underlying pathologic and virologic mechanisms of an HEV gt1 infection during pregnancy remain largely undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal mortality rates of about 25% in association with fulminant hepatic failure have been observed in HEV‐infected pregnant women,18 and the human placenta was also implicated as an extrahepatic replication site of HEV. Notably, vertical transmission has been shown to occur frequently,19 and adverse fetal outcome, especially in the third trimester, include preterm delivery, abortion, stillbirth, and intrauterine fetal and neonatal death 18, 20, 21. However, the underlying pathologic and virologic mechanisms of an HEV gt1 infection during pregnancy remain largely undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports evaluating etiological spectrum in individuals with acute hepatitis during both epidemic and sporadic settings indicate three distinct observations in India: 1) HEV is the commonest cause of AVH in both sporadic and epidemic settings [3][4][5][6][7][8][9][10] 2) The frequency of HEV as the cause of AVH is significantly higher among pregnant females than in non-pregnant females and males 24,25,[42][43][44][45][46][47] 3) The frequency of ALF is significantly higher in pregnant females than in non-pregnant females and males with HEV infection. 7,24,25,43,45 Tables 3 and 4 7,11,12,[42][43][44][45][46][48][49][50] highlight the sporadic and epidemic studies of HEV induced AVH/ALF reported in pregnant females.…”
Section: Pregnant Females Are More Susceptible To Contract Hepatitis mentioning
confidence: 99%
“…7,24,25,43,45 Tables 3 and 4 7,11,12,[42][43][44][45][46][48][49][50] highlight the sporadic and epidemic studies of HEV induced AVH/ALF reported in pregnant females.…”
Section: Pregnant Females Are More Susceptible To Contract Hepatitis mentioning
confidence: 99%
See 2 more Smart Citations